Planned Unit Development (PUD) in Urban Design Project - Sapsangthong, Akarawit; Horayangkura, Vimolsiddhi; Shekutkovska Dokoska, Aleksandra (Journal of Architectural/Planning Research and Studies (JARS), 2020)
Since 1960s Bangkok has been under the practices of post-war urban planning, in addition to a series of initial development of comprehensive plans, through four versions of adopted comprehensive plans which were used as urban development controlling tool, while lacking regulations for urban guidance. Planned Unit Development (PUD) is a regulation allowing comprehensive planning and design on a specific large urban area with flexibility for greater livability. This research aims to explore the applicability of PUD in the urban development process of Bangkok. Two conceptual design scenarios for applying PUD were generated providing project feasibility analysis and PUD design guidelines. The research is conducted as an experimental study focusing on the tasks of three variables: scenario generation, feasibility analysis, and urban design and development. The design experimentation result has been stated that it potentially applies PUD on the study site (Pahonyothin 19/1, Bangkok). However, it will require great financial aid and a period of time. With PUD, Bangkok urbanization can reach the stage of urban design that contributes variable benefits such as site planning and design, density modification, providing infrastructures, and circulation improvement. In addition, PUD provides greater ranges of benefits such as carbon reduction, urban heat island mitigation, promoting Transit Oriented Development (TOD), and positioning on SDG 11: Sustainable Cities and Communities. The research output is providing guidelines towards a sustainable 21st century city for Bangkok.